Sensitization of Tio2 nanostructures for photoelectrochemcial hydrogen generation - Luo, Jingshan (2014)
Energy is an eternal research topic concerning the continuous development of our society and daily life. Finding a sustainable, green and efficient way to harvest, store and use the energy is highly demanded. This thesis is part of my research efforts for developing efficient and low cost material systems for energy conversion and storage. With the inspiration from my undergraduate experiences in quantum dots synthesis, I have decided to choose the sensitization of TiO2 with short band gap semiconductors for photoelectrochemical (PEC) hydrogen generation as my research topic. This thesis contains mainly three parts, chapter 1, chapters 2-4 and chapter 5. Chapter 1 is a general introduction, focusing on three parts: an overview of the energy demands and challenges, an introduction of the basic principles and working mechanisms of the PEC cell, and a short review of the recent advancement of using TiO2 for PEC hydrogen generation. Chapter 2-4 are the main body of the thesis, which describes the experiments and strategies I have carried out and developed to improve the efficiency of hydrogen generation. In specific, chapter 2 is focused on the study of different kinds of sensitizers, their optical properties, band edge positions, electron injection efficiencies and stability for PEC hydrogen generation. Studying these properties provides a physical background for the design of efficient PEC system. Chapter 3 is focused on improving the surface area of TiO2. TiO2 inverse opal has attracts wide attention in the application of dye sensitized solar cell and semiconductor sensitized solar cell due to its unique three-dimensional structure. However, its surface area is still low, thus the efficiency is low compared to the conventional TiO2 nanoparticles. In this chapter, we try to improve the surface area of TiO2 inverse opal by further growth of ZnO nanowires inside. The higher surface area would result in higher amount of sensitizer loading and more active sites for water splitting reactions. Thus the CdS sensitized hierarchical structure shows nearly double photocurrent of the pristine TiO2 inverse opal with CdS sensitization. In chapter 4, a new sensitization method ALDIER based on atomic layer deposition (ALD) and ion exchange reaction (IER) has been developed. Deep penetration of the sensitizers into the complex nanostructures has been a challenge for a long time in improving the efficiency of short band gap semiconductor sensitized device. This is mainly due to the large size of the sensitizer and the high aspect ratio of the complex nanostructure for sensitization. ALD is a powerful thin film deposition technique, which could provide homogeneous coating on high aspect ratio nanostructures with excellent step coverage. However, direct deposition of the sensitizers by ALD is limited by the toxic precursors and complex processes. An indirect way by IER with the well-developed ZnO by ALD provides a great versatility for choosing different sensitizers. The newly developed ALDIER method in this chapter by combining the two powerful techniques together shows more than double the performance of the conventional successive ionic layer adsorption and reaction (SILAR) method, which solves the penetration challenge for sensitization. Chapter 5 concludes the whole thesis in a general way with the comments of the problems existed in the current material systems, as well as the recommendations for the future efforts in overcoming the challenges and improving the efficiency of PEC cell for hydrogen generation. In summary, this thesis studies the basic physical properties of the materials regarding the efficiency for PEC hydrogen generation first, and then provides two practical strategies to improve the efficiency by tailoring the TiO2 nanostructures and improving the sensitizer deposition method, respectively. I hope this thesis could provide some useful information and ideas for the other researchers.